Earnings Supplements and Job Quality among Former Welfare Recipients: Evidence from the Self-Sufficiency Project - Foley, Kelly; Schwartz, Saul (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2003)
SummaryThe Self-Sufficiency Project (SSP) offered a generous but time-limited earnings supplement to a randomly assigned group of lone parents—who were also long-term social assistance recipients—if they found full-time work and left social assistance. Employment data was collected for this group over a three-year period following the offer, and for a randomly-assigned control group. This article analyzes the characteristics of the first job that SSP participants found after they left social assistance. The occupations and industries of the first job held are analyzed as is SSP’s impact on hourly wages, weekly hours and job stability. The article finds that SSP increased employment in jobs that were no worse (and no better) than the jobs that participants might have taken in the absence of the program.